Properties of the yrast levels of 78-82Sr even-even isotops - Emad Mamdouh; Wafaa Mohammad Najeebb (College of Education for Pure Sciences, 2010)
Abstract: The properties of the yrast levels of 78-82Sr even-even isotopes have been studied. The method of gamma energy over spin (E-GOS) has been used to analyze the energy levels of these isotopes which shows that the two isotopes 78 Sr and 80Sr lie in the γ-unstable, O(6), limit, but 82Sr isotope lies in the transition region (SU(5)→SU(3)). The interacting boson model IBM-1 has been used to calculate the energy levels for these three isotopes each for the limit it lies and a comparision with the experimental data is done and shows a good agreement. The backbending in the energy levels for 80Sr and 82Sr are observed but not for 78Sr.